Test and Validation of a Multi-Block Solution for Improved Tracking in Outdoor Scenarios: A Case Study in the Pinocchio Park - Massimo Magrini; Fabrizio Matarese; Davide Moroni (Information, 2022)
Augmented reality techniques have recently found many applications in the field of cultural heritage. When used in outdoor scenarios, however, this technology can face several issues, mainly due to unstable light conditions, jeopardizing the users’ experience. Various solutions to this problem have been proposed in the literature; however, none of them are fully effective. This paper introduces a solution based on a multi-block image target segmentation and a dedicated add-on for the Unity3D game engine. After tests in the lab, the solution was validated in a real scenario at Pinocchio Park (Collodi, Italy), using two different Augmented Reality (AR) libraries and comparing it to a standard methodology. Quantitative results show that the proposed approach provides superior performance and usability. Although the proposed solution is still open to improvement, it combines effectiveness and ease of implementation without any drawbacks.